Orientation and Spatial Frequency Selectivity following Adaptation: A Reaction Time Study. (March 2015) - Plainis, Sotiris; Parry, Neil R A; Sapountzis, Panagiotis; Murray, Ian J
The aim of the study was to determine orientation and spatial frequency sensitivity using reaction times (RTs) in an adaptation paradigm. Simple RTs were measured to the onset of a Gabor patch (SD = 1.2 deg, spatial frequency = 4 cycles deg −1 ). Observers adapted for 10 s to a 4 cycles deg −1 grating presented at a series of orientations (0, 2, 5, 10, 22.5, 45, 90°) or spatial frequencies (±0.5, 1, and 2 octaves). The contrast of the test grating was 4x each participant's unadapted threshold. The effect of adaptation was evaluated by transforming RTs to effective contrast reduction using RT-based contrast response functions. RTs increased by between ∼ 100 ms to 150 ms when the test and adapting gratings were of the same orientation or spatial frequency. The effect became less pronounced as the difference in orientation or spatial frequency increased. The average bandwidths for orientation and spatial frequency were 17.4° and 1.24 octaves, respectively. The method has some advantages over traditional approaches. It reveals a rapid time course of adaptation recovery with a half-life of about 13 s to 23 s. RTs form a rapid and easily implemented technique for assessing the underlying physiological mechanisms that control adaptation at suprathreshold levels of contrast.